A global functional analysis of missense mutations reveals two major hotspots in the PALB2 tumor suppressor. Issue 20 (5th October 2019) - Rodrigue, Amélie; Margaillan, Guillaume; Torres Gomes, Thiago; Coulombe, Yan; Montalban, Gemma; da Costa e Silva Carvalho, Simone; Milano, Larissa; Ducy, Mandy; De-Gregoriis, Giuliana; Dellaire, Graham; Araújo da Silva Jr, Wilson; Monteiro, Alvaro N; et al.
Abstract: While biallelic mutations in the PALB2 tumor suppressor cause Fanconi anemia subtype FA-N, monoallelic mutations predispose to breast and familial pancreatic cancer. Although hundreds of missense variants in PALB2 have been identified in patients to date, only a few have clear functional and clinical relevance. Herein, we investigate the effects of 44 PALB2 variants of uncertain significance found in breast cancer patients and provide detailed analysis by systematic functional assays. Our comprehensive functional analysis reveals two hotspots for potentially deleterious variations within PALB2, one at each terminus. PALB2 N-terminus variants p.P8L [c.23C>T], p.Y28C [c.83A>G], and p.R37H [c.110G>A] compromised PALB2-mediated homologous recombination. At the C-terminus, PALB2 variants p.L947F [c.2841G>T], p.L947S [c.2840T>C], and most strikingly p.T1030I [c.3089C>T] and p.W1140G [c.3418T>C], stood out with pronounced PARP inhibitor sensitivity and cytoplasmic accumulation in addition to marked defects in recruitment to DNA damage sites, interaction with BRCA2 and homologous recombination. Altogether, our findings show that a combination of functional assays is necessary to assess the impact of germline missense variants on PALB2 function, in order to guide proper classification of their deleteriousness.